Aspectos socioeconômicos, culturais e ambientais presentes no suicídio de trabalhadores e trabalhadoras inseridos no agronegócio - Costa, Virgínia Luiza Silva (2018)
Suicide is a public health problem, shown by the increasing number of death from this cause in the world, in Brazil, and also in Mato Grosso in recent years. This phenomenon is not the result of a single reason or cause. It is the result of a complex interaction between diverse factors, such as biological, genetic, psychological, social, cultural, environmental and labor. It is understood as a socio-historical phenomenon, for it displays specific characteristics and assumes different fashions at different moments in history. It is pointed out that the young population is the most vulnerable to suicidal behavior, but statistics do not consider working as a key determinant in cases of suicide, since the young population‟s labor market inclusion or exclusion exerts its influence on the occurrence of these suicides, specially in the rural population. Objective: This study aims to understand the socioeconomic, cultural and environmental aspects present in suicide of workers entered in agribusiness and its implications for the surveillance and protection of health practices. Methodology: This is an exploratory research with a qualitative approach. The suicide data from Mato Grosso was set up by means of SIM by the Self-reported Morbidity Survey, from the cities studied, that have large agricultural production, where the cases of suicide were located for the execution of psychosocial autopsy with informants. Results: According to SIM data, in 2014, 154 cases of self-inflicted deaths occurred among people over the age of 15 in Mato Grosso. According to the Self-reported Morbidity Survey, 17 cases of suicide were located in the sample of 1,384 interviewed families in the three municipalities of the study. Finally, five cases of suicide were reconstructed from eight psychosocial autopsy interviews, with close informants, such as mother, sister, aunt, brother-in-law, teacher, neighbor and coworkers. Aspects that have been identified in cases of suicide were divided into three blocks: (a) socioeconomic they were recognized the precarious working conditions, migration for want of subsistence, abusive work, child labor, addiction (alcoholism), lack of access to leisure and health services and lack of support from companies to promote mental health; (b) cultural where it was perceived family conflicts, social isolation, recent divorce, machismo and patriarchy, magical-religious explanations for the causes of suicide, discrimination and resistance to psychosocial, psychological and psychiatric care, the agribusiness culture that dominates the area and silences cases of mental illness and suicide; (c) environmental in which it highlights to pesticides exposure and poisoning, small or medium-sized cities with strong social control and proximity of plantations to houses, schools and commerce. Conclusion: When seeking to unveil economic, social and environmental aspects, as a track for understanding suicide, we realize that the process of work in agribusiness, associated with other factors such as migration, exposure to pesticides, the hegemony in the control of territory and interpersonal relationships, influence directly on the decision-making of individuals, and increase suffering that results in suicide.